Protein delivery to vacuole requires SAND protein-dependent rab GTPase conversion for MVB-vacuole fusion - Singh, Manoj Kumar; Schumacher, Karin (Current biology, 2014)
Summary Plasma-membrane proteins such as ligand-binding receptor kinases, ion channels, or nutrient transporters are turned over by targeting to a lytic compartment—lysosome or vacuole—for degradation. After their internalization, these proteins arrive at an early endosome, which then matures into a late endosome with intraluminal vesicles (multivesicular body, MVB) before fusing with the lysosome/vacuole in animals or yeast [1, 2]. The endosomal maturation step involves a SAND family protein mediating Rab5-to-Rab7 GTPase conversion [3]. Vacuolar trafficking is much less well understood in plants [4-6]. Here we analyze the role of the single-copy SAND gene of Arabidopsis. In contrast to its animal or yeast counterpart, Arabidopsis SAND protein is not required for early-to-late endosomal maturation, although its role in mediating Rab5-to-Rab7 conversion is conserved. Instead, Arabidopsis SAND protein is essential for the subsequent fusion of MVBs with the vacuole. The inability of sand mutant to mediate MVB-vacuole fusion is not caused by the continued Rab5 activity but rather reflects the failure to activate Rab7. In conclusion, regarding the endosomal passage of cargo proteins for degradation, a major difference between plants and nonplant organisms might result from the relative timing of endosomal maturation and SAND-dependent Rab GTPase conversion as a prerequisite for the fusion of late endosomes/MVBs with the lysosome/vacuole.